SAE Technical Paper Series 1999
DOI: 10.4271/1999-01-1508
|View full text |Cite
|
Sign up to set email alerts
|

Methylal and Methylal-Diesel Blended Fuels for Use in Compression-Ignition Engines

Abstract: ABSTRACT"Gas-to-liquids" catalytic conversion technologies show promise for liberating stranded natural gas reserves and for achieving energy diversity worldwide. Some gas-toliquids products are used as transportation fuels and as blendstocks for upgrading crudederived fuels. Methylal(CHs-0-CHz-0-CH& also known as dimethoxymethane or DMM, is a gas-to-liquid chemical that has been evaluated for use as a diesel fuel component. Methylal contains 42% oxygen by weight and is soluble in diesel fuel. The physical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 15 publications
1
43
0
Order By: Relevance
“…Taking into account their high auto-ignition tendency and high oxygen content, dimethoxymethane [2,3] and 1,2-dimethoxyethane [1] were chosen as good fuels or fuel additives.…”
mentioning
confidence: 99%
“…Taking into account their high auto-ignition tendency and high oxygen content, dimethoxymethane [2,3] and 1,2-dimethoxyethane [1] were chosen as good fuels or fuel additives.…”
mentioning
confidence: 99%
“…2 The capability of oxygenates to reduce emissions from diesel fuels has also been investigated. 1,[5][6][7] Particularly, of the potential diesel fuel components, diethylene glycol dimethyl ether (DEDM, molecular structure: CH 3 OCH 2 CH 2 OCH 2 CH 2 OCH 3 , also known as diglyme) has been tested both as a pure chemical 8,9 and as a fuel component blended with diesel fuel. 10,11 However, most of the existing work has focused on monitoring benefits of oxygenates in reducing regulated emissions, namely, PM, NO x , CO, and total hydrocarbon (THC).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, thanks to this enlarged mechanism, we have been able to establish the kinetics of the combustion of ethylal practically unknown until now. This investigation on these diethers will help to understand the experimental results obtained by engine manufacturers which have added methylal in their diesel fuel [1][2][3][4][5][6]. They observed a decrease of the formation of soot particles.…”
Section: Discussionmentioning
confidence: 95%
“…It emitted 52% lower particulate matter and 4% lower nitrogen oxides compared to a conventional diesel fuel. Vertin et al [4] have demonstrated a substantial reduction of particulate matter emissions for 10-30% blends of methylal in diesel fuel. And, Cheng et al [5] showed that the presence of methylal in diesel has reduced the total particle mass concentrations, as well as the particle number density and the mean particle diameter.…”
Section: Introductionmentioning
confidence: 98%